2018
DOI: 10.1002/ehf2.12309
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of integrated device diagnostics for heart failure management: results of the TRIAGE‐HF study

Abstract: AimsThe primary aim of the TRIAGE‐HF trial was to correlate cardiac implantable electronic device‐generated heart failure risk status (HFRS) with signs, symptoms, and patient behaviours classically associated with worsening heart failure (HF).Methods and resultsTRIAGE‐HF enrolled 100 subjects with systolic HF implanted with a Medtronic high‐performance device and followed up at three Canadian HF centres. Study follow‐up was up to 8 months. The HFRS assigned each subject's overall risk of HF hospitalization in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 20 publications
1
46
0
1
Order By: Relevance
“…Previous literature has showed that the integrated ICD diagnostics included in our study, individually and in combination, were able to identify patients at risk of adverse outcomes such as heart failure hospitalization and mortality. [18][19][20][21][22][23] The specific ICD physiological parameters employed in the current study were selected given their strongest effect on clinical outcomes based on prior research. 24 Catanzariti et al showed monitoring thoracic impedance reduced hospitalization related to heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has showed that the integrated ICD diagnostics included in our study, individually and in combination, were able to identify patients at risk of adverse outcomes such as heart failure hospitalization and mortality. [18][19][20][21][22][23] The specific ICD physiological parameters employed in the current study were selected given their strongest effect on clinical outcomes based on prior research. 24 Catanzariti et al showed monitoring thoracic impedance reduced hospitalization related to heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of asymptomatic deterioration would effectively take the place following a physical examination performed in the clinic and may involve the use of simple measures such as weight and blood pressure, but may also expand in suitable patients to involve more advanced metrics such as implantable sensor data (e.g. CardioMEMS™ [50], OptiVol™ [63]). Effective monitoring may be improved by novel eHealth technology and sensors, which is a rapidly growing field.…”
Section: The Hf Paradigm Shift To Pppmmentioning
confidence: 99%
“…The Program to Access and Review Trending Information and Evaluate Correlation to Symptoms in Patients With Heart Failure (PARTNERS HF) and Integrated Diagnostic for Heart Failure (TRIAGE-HF) trials have shown promise in identifying which patients are at risk of hospitalisation. [28,29]…”
Section: Evidence For the Benefit Of Telemonitoring Technologiesmentioning
confidence: 99%